Developing and applying a training needs analysis tool for healthcare workers managing snakebite envenoming: A cross-sectional study in Eswatini. - Jonathan Steinhorst; Clare Baker; Sara Padidar; Thea Litschka-Koen; Ezekiel Ngwenya; Lindelwa Mmema; Brent Thomas; Nondumiso Shongwe; Trevor Sithole; Mbongiseni Mathobela; Anna Trelfa; Nicholas R Casewell; et al. (PLoS Neglected Tropical Diseases)
A considerable number of patients present to hospitals in Eswatini each year following bites by venomous snakes. Effectively diagnosing and treating patients with snakebite envenoming requires healthcare workers to have a variety of generic and snakebite-specific medical skills. In several countries, however, healthcare workers have been found to have limited skills in managing snakebite patients. We used the Delphi method to adapt the Hennessy-Hicks training needs analysis questionnaire to the context of snakebite envenoming and subsequently used the adapted questionnaire to assess the self-perceived training needs of 90 healthcare workers from ten hospitals in Eswatini. Two-thirds (63%) of participants were nursing staff and one third (34%) medical doctors. Overall, 74% of healthcare workers had previously received training on snakebite. Although a training need was reported for all skills included in the survey, the extent of the training need varied between different skills and groups of healthcare workers. The highest average training need was registered in the domains 'research and audit' and 'clinical tasks' with the latter accounting for nine of the ten skills with the highest training need. Nurses reported a higher training need than doctors, especially for clinical tasks. Receiving snakebite training before as well as after obtaining the primary qualification was associated with the lowest average training need, particularly in clinical skills. Ninety-three percent of interviewed healthcare workers would welcome more frequent training opportunities on the clinical management of snakebite patients. This newly developed snakebite training needs analysis tool can aid in adapting training initiatives to a dynamic and evolving healthcare workforce and it is designed to be transferrable to snakebite endemic settings worldwide.